Vliv koncepce dějin F. Palackého na soudobou historickou prózu - Čížková, Jitka (Jihočeská univerzita, 2011)
Diplomová práce přináší příspěvek k problematice inspirace historické prózy devatenáctého století odbornou dějepisnou literaturou. Jejím úkolem je zhodnocení provázanosti Palackého husitské koncepce s vybranými dvěma povídkami Josefa Kajetána Tyla, jejichž děj je situován do první poloviny patnáctého století v Čechách. První část diplomové práce uvádí stručnou charakteristiku obou autorů a jejich tvorby s historickou tematikou. Následující teoretická kapitola je věnována pohledu na husitství v devatenáctém století. Druhá část práce je zaměřena prakticky, neboť vedle srovnání výkladu dějin oběma autory také obsahuje subjektivní interpretaci literárních kvalit postav a okolností, jež si Tyl domýšlí.
The influence of the historical Concept of František Palacký in the contemporary novelistic
Keywords: This diploma thesis brings a report on the questions of the inspiration of the 19th century historical prose by the specialised literature. Its aim is to evaluate the links of the Hussite conception by Palacký with two short stories by Josef Kajetán Tyl; whose plot is situated to the first half of the 15th century in Bohemia. The first part deals with the short characteristics of the two authors and their historical works. The following theoretical chapter is devoted to their attitude to the Hussite movement in the 19th century. The second part of the work focuses on practical issues as it takes in account not just the comparison of the two author´s views of the history but also the subjective interpretation of the literal aims of the characters and events that are presumed by Tyl.